DEVELOPMENT WRITTEN TEST ASSESSMENT BASED ON INTEGRATED THEMATIC LEARNING FOR V GRADE STUDENTS OF ELEMENTARY SCHOOL - Rochmiyati Rochmiyati; Aminah Aminah (Teunuleh Publisher, 2021)
Development Written Test Assessment Based on Integrated Thematic Learning for V Grade Students of Elementary School. This was an integrated learning method for elementary school and to know the difficulty level, differentiation, distract, validity and reliability. The research populations were V grade students of Elementary School, Pringsewu District, Lampung Province, Indonesia. This research used research and development methods adapted with the steps according to Borg & Gall. The data collection tool used questionnaires and tests. Data analysis techniques by expert validation and test instruments were analyzed with validity, reliability, difficulty, differentiation, and distract. The validation assessment results, material and linguistic experts on question instruments were developed very well, and were worthy of use. The results of large-scale test of product development and the results of the instrument Keywords: assessment, integrated thematic learning, written test.